2021
DOI: 10.1159/000514323
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pycnogenol® Intake Benefits the Skin in Urban Chinese Outdoor Workers: A Randomized, Placebo-Controlled, Double-Blind, and Crossover Intervention Study

Abstract: <b><i>Background:</i></b> Oral supplementation with a standardized extract from the bark of the French pine (Pycnogenol®) has been reported to benefit the skin. It might thus represent an easy-to-use strategy to improve the skin health of individuals who are exposed to considerable environmental stress in large urban areas. <b><i>Objective:</i></b> We investigated if oral intake of Pycnogenol® can benefit the skin of Han Chinese working outdoors in Beijing, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similarly, a significant improvement of TEWL was recently shown for urban outdoor workers in a randomized, placebo-controlled, double blind, cross-over intervention study after taking 2 × 50 mg Pycnogenol ® over a period of 3 months in autumn in Shanghai. 35 In that study, a significant effect of Pycnogenol ® on TEWL was only observed in the group, consuming the Pycnogenol ® in the moderate season pointing to the seasonality of that parameter.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, a significant improvement of TEWL was recently shown for urban outdoor workers in a randomized, placebo-controlled, double blind, cross-over intervention study after taking 2 × 50 mg Pycnogenol ® over a period of 3 months in autumn in Shanghai. 35 In that study, a significant effect of Pycnogenol ® on TEWL was only observed in the group, consuming the Pycnogenol ® in the moderate season pointing to the seasonality of that parameter.…”
Section: Resultsmentioning
confidence: 76%
“…Anti-inflammatory action of Pycnogenol ® , like the reduction of inflammation mediators was shown in RDP trials on joint health as well as on respiratory health ( 40 , 49 ). Pycnogenol ® ’s favorable impact on blood circulation was demonstrated in multiple ways, like the improvement of endothelial function or microcirculation in clinical RDP trials on cardiovascular health, chronic venous insufficiency, on skin and hair health, eye health and menopause ( 9 , 11 , 12 , 20 22 , 28 33 , 43 – 47 ). Improved skin elasticity, skin moisture, joint flexibility and hair health illustrate the beneficial effects of Pycnogenol ® on the extracellular matrix, observed in RDP studies ( 40 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on skin health and one recently published study on hair quality have shown Pycnogenol ® ’s effects on beauty and skin health in RDP setups ( 43 , 44 ).…”
Section: Randomized Double-blind Placebo-controlled Human Clinical St...mentioning
confidence: 99%
See 1 more Smart Citation
“…French maritime pine ( Pinus pinaster ) bark extract is a plant extract containing proanthocyanidins and other antioxidant compounds. Oral Pycnogenol (the standardized extract) [ 85 ] in association with broad-spectrum sunscreen [ 86 ] has been shown to be effective in the treatment of facial melasma, and was also found to prevent skin darkening in Chinese outdoor workers [ 87 ].…”
Section: Preventing and Treating Hyperpigmentation In The Context Of ...mentioning
confidence: 99%